Izolacjonizm i appeasement: Waszyngton i Londyn wobec imperium sowieckiego oraz polskiego kryzysu latem 1920 r. - Nowak, Andrzej (Kwartalnik Historyczny, 2014)
Isolationism and Appeasement: Washington and London vis-à-vis the Soviet Empire and the Polish Crisis in the Summer of 1920 The article analyses the attitude of the political elites of the USA and Great Britain towards the question of Russia and the Soviet Union in the summer of 1920. The analysis is based on the B. Colby Papers associated with the US Secretary of State Bainbridge Colby, as well as material concerning President Woodrow Wilson (the Congress Library in Washington), together with heretofore unexamined documents regarding Philipp Kerr, private secretary to the British Prime Minister David Lloyd George and the actual éminence gris of his cabinet (P. Kerr Papers, National Archives of Scotland, Edinburgh) and the Cabinet Papers at the National Archives in London. From January 1920 Lloyd George conducted a consistent policy of maintaining an agreement with Soviet Russia, known as “peace through trade”. Its culmination was an invitation to London issued to a political delegation headed by Lev Kamenev, member of the Political Bureau. At the same time, the United States withdrew from active policy in Europe after the Senate rejected the Versailles Treaty. Within this context the author analysed the reaction of the Wilson Administration and the Lloyd George cabinet towards Soviet aggression in Central Europe, when in August 1920 the Red Army reached Warsaw and Lenin proclaimed the Sovietisation of Poland. The British response to this challenge to the entire Versailles system assumed the form of a decision made by Lloyd George (also on 10 August 1920), urging Poland to capitulate in the face of the demands formulated by Moscow. By relinquishing Poland to the Soviet empire the British prime minister hoped to achieve reconciliation with Lenin at a diplomatic conference that was to take place in London in the autumn of 1920. The Americans responded to Soviet aggression by declaring passivity, announced by Bainbridge Colby in his famous note of 10 August. The author presented the origin of this act as well as the motives for the Lloyd George resolution conceived as an historical prefiguration of the isolationism policy (in the case of the USA) and appeasement (in the case of Great Britain).